2016
DOI: 10.1158/0008-5472.can-15-2073
|View full text |Cite|
|
Sign up to set email alerts
|

Delivery of Therapeutics Targeting the mRNA-Binding Protein HuR Using 3DNA Nanocarriers Suppresses Ovarian Tumor Growth

Abstract: Growing evidence shows that cancer cells use mRNA-binding proteins and miRNAs to posttranscriptionally regulate signaling pathways to adapt to harsh tumor microenvironments. In ovarian cancer, cytoplasmic accumulation of mRNA-binding protein HuR (ELAVL1) is associated with poor prognosis. In this study, we observed high HuR expression in ovarian cancer cells compared with ovarian primary cells, providing a rationale for targeting HuR. RNAi-mediated silencing of HuR in ovarian cancer cells significantly decreas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 50 publications
3
61
0
1
Order By: Relevance
“…Logically, the therapeutic strategies to inhibit HuR, especially in CRC, would be to: 1) silence expression levels [53], 2) disrupt the ARE-binding activity which is mediated through the conserved RNA recognition motifs (RRM) domains of HuR, and 3) inhibit HuR nuclear to cytoplasmic translocation. In this study, we explored MS-444, originally identified as a HuR inhibitor in a confocal high-throughput screen of microbial, mycological, and plant extracts [21], wherein MS-444 was successful in disrupting binding between HuR and its ARE-containing mRNA targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logically, the therapeutic strategies to inhibit HuR, especially in CRC, would be to: 1) silence expression levels [53], 2) disrupt the ARE-binding activity which is mediated through the conserved RNA recognition motifs (RRM) domains of HuR, and 3) inhibit HuR nuclear to cytoplasmic translocation. In this study, we explored MS-444, originally identified as a HuR inhibitor in a confocal high-throughput screen of microbial, mycological, and plant extracts [21], wherein MS-444 was successful in disrupting binding between HuR and its ARE-containing mRNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…Further efforts to evaluate these findings in CRC models as a means to identify clinically available targeted and cytotoxic therapies that would synergize with HuR targeted therapy are in progress. These efforts, along with other modes of HuR inhibition (i.e., targeted siRNA delivery [53]), being evaluated in pre-clinical models for: 1) targeting specificity, 2) toxicity profiles, and 3) therapeutic effects against malignant phenotypes, will further support the notion that HuR is a valuable target in CRC and that pharmacological HuR inhibitors such as MS-444 warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, therapeutic administration of a molecular-targeted inhibitor of HuR in the setting of PDA could potentially have a major clinical benefit when combined with TRAIL or DR agonists, or in combination with most other anti-cancer (e.g., chemotherapeutic) agents (6, 29, 33) whose activity relies on activation of intrinsic or extrinsic apoptotic pathways (52). Ongoing studies are exploring alternative approaches of inhibiting HuR that could easily be incorporated in a regimen that includes TRAIL (53, 54). …”
Section: Discussionmentioning
confidence: 99%
“…Supramolecular chemistry enables noncovalent assembly of individual molecular building blocks (e.g., small-molecule prodrug entities, sensing molecules), thus providing innovative approaches to the creation of fascinating nanostructures for biomedical application (7)(8)(9)(10)(11)(12)(13)(14). For example, Hamachi and colleagues developed a novel sensing mechanism for selective protein detection based on the self-assembly of small amphiphilic probes (9,10,15).…”
Section: Introductionmentioning
confidence: 99%